Computational Fluid Dynamics for Assessment of Airflow Patterns in the Airway Tree - Legendre, Daniel Formariz; Lucente, Gustavo Sensaki; Uemoto, Vinicius Ruiz; Minamoto, Helio; Ito, Cristiane Yumi Koga [UNESP]; da Silva, Bruno Utiyama; de Freitas, Renata Valeri; Cardoso, Paulo Francisco Guerreiro; Moriya, Henrique Takachi; Aoki, Fabio Gava (Springer Nature, 2024)
Tracheal stenosis lesions have a negative impact on patients’ quality of life. The incidence of post-intubation tracheal stenosis ranges from 6 to 20%, and after tracheostomy from 0.6 to 21%. Since the symptoms are only noticeable after the presence of a 70% reduction in the tracheal lumen, early diagnosis is not always possible. Computed tomography (CT) scan can be used to assess stenosis even before symptoms appear, however it is unable to provide dynamic data (e.g., airflow and pressure patterns) that would be important in early diagnosis, as well as for prognostic assessment and therapeutic planning. Computational Fluid Dynamics (CFD) is a non-invasive analysis that allows computer simulations of airflow using reconstructions based on CT scan images. We hypothesize that CFD simulation can be a feasible tool to assess the fluid-mechanical behavior within the tracheal stenosis. Results of the streamlines allowed us to understand the flow pattern present along the trachea. In addition, it was possible to identify the occurrence of vortex in the proximal region of the trachea that precedes the stenosis and in the left bronchus also affected by stenosis. The assessment of pressure gradient and WSS values may provide additional information for risk estimating to the tracheal wall.
Keywords: CT scan; Image segmentation and computational fluid dynamics; Tracheal stenosis